Government debt management in the euro area - recent theoretical developments and changes in practices - Guido Wolswijk; Jakob de Haan (European Central Bank (ECB), 2005)
This paper reviews recent developments in the management of government debt in the euro area, covering both theoretical and practical aspects. It focuses on key aspects of debt management; the objectives of debt management, its organisation, the maturity of debt, inflation-indexation, currency-denomination, the ownership of debt, and debt issuing and trading practices. Main adjustments include an increase in autonomy of debt management agencies, and a convergence in debt maturities and in debt issuing strategies. Issuance of inflation-indexed bonds and the use of interest rate swaps have increased strongly. While the share of government debt denominated in non-domestic currencies is falling, foreign ownership of euro area government debt is increasing markedly. The observed changes in recent years in part reflect the introduction of the euro and the related integration of European capital markets.
Keywords: 330; Schuldenmanagement; Öffentliche Schulden; Theorie; EU-Staaten